Afraid to die [compact disc, unabridged] - Jackson, Lisa (Jackson, Lisa. Selena Alvarez/Regan Pescoli novels., 2012)
The town of Grizzly Falls is on edge in the wake of a serial killer, and Detective Selena Alvarez is no exception. There are two victims so far-- their bodies found frozen solid and deliberately displayed. Both are women she knew and each wears a piece of Selena's jewelry.